STRATEGI KOMUNIKASI PEMERINTAH DALAM MENINGKATKAN PELAYANAN PUBLIK: (Studi Pada Kecamatan Poncokusumo Kab.Malang) - Soeltanto, Taufiq; Utami, Wiwik; Ratu, Iwan Pura Tagu; Hadiwiyono, Hadiwiyono (JOURNAL AKSES STIA MALANG, 2025)
Government communication is essentially just human contact that occurs within the framework of government agencies. Because this process involves the exchange of messages through interdependent formal networks. The problem of the people of Poncokusumo District, Malang Regency who do not receive enough information from the government was the trigger for this research. Some examples of incorrect information include services with unclear completion periods, services that are not interactive, and services with service processes that are not transparent, whether displayed openly on information boards or provided secretly. This research aims to determine the relationship between government communication and the quality of public administration services to the community in Poncokusumo District, Malang Regency. This research uses a qualitative descriptive methodology and collects data through documentation, interviews and observation. Based on the results of the author's research, the PoncokusumoDistrict Office uses various communication techniques, such as choosing the right language and message style, choosing the right media and channels, and resolving communication barriers. The act of defending the rights and interests of other people carried out by an individual or group of people using certain methods, processes and tactics in accordance with standards is considered a form of public service